Coding the fictional characters in the novels of Ahmed Khalaf (Journal of the College of Basic Education, 2023)
The novelist used the creation in the narration of events, in their external and internal appearance in their symbolic dimension, conscious and regular with artificial mechanisms of reality, which embodied the effectiveness of events gaining meanings between symbols and interpretation.